Efficient non-enzymatic cleavage of Staphylococcus aureus plasmid DNAs mediated by neodymium ions - Zovčáková, Monika; Španová, Alena; Pantůček, Roman; Doškař, Jiří; Rittich, Bohuslav (Analytical biochemistry, 2016)
Staphylococcus aureus plasmids are the main factor in the spreading of antibacterial resistance among bacterial strains that has emerged on a worldwide scale. Plasmids recovered from 12 clinical and food isolates of S. aureus were treated with 10 mM free lanthanide Nd(3+) ions (non-enzymatic cleavage agent) in Hepes buffer (pH 7.5) at 70 °C. Topological forms of plasmids-closed circular (ccc), open circular (oc), and linear (lin)-produced by cleavage at different times were separated using pulsed-field agarose gel electrophoresis. The method is proposed to detect and differentiate several plasmids in the same bacterial strain according to their size.
Keywords: Staphylococcus aureus; neodym; Neodymium; DNA bakterií; DNA, Bacterial; Plasmids; ionty; plazmidy; Ions